1998
DOI: 10.1159/000055473
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Cytokines by Human Choroidal Melanoma Cells and Skin Melanoma Cell Lines in vitro

Abstract: The selective secretion of interleukin 6 (IL-6), interleukin 8 (IL-8), interleukin 10 (IL-10), basic fibroblast growth factor (b-FGF) and transforming growth factor beta 1 (TGFβ-1) in tissue culture of choroidal melanomas and two established skin melanoma cell lines was investigated with ELISA analysis. Values of choroidal melanoma cells were compared with the melanoma cell lines and human fibroblasts as a physiological control. High secretion of IL-6 was detectable in choroidal melanoma cultures but not in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Recently, we demonstrated that choroidal melanoma cells secrete a variety of cytokines in vitro [6]. Interestingly, the secretion of IL-6 and IL-8, both known as proinflammatory factors, is strongly up-regulated in malignant melanoma cell lines and in choroidal melanoma cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that choroidal melanoma cells secrete a variety of cytokines in vitro [6]. Interestingly, the secretion of IL-6 and IL-8, both known as proinflammatory factors, is strongly up-regulated in malignant melanoma cell lines and in choroidal melanoma cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…After injury to the choroid/retina, RPE cells are exposed to a variety of growth factors and cytokines from the serum, resulting in cell proliferation. RPE cell proliferation is an important step in the pathogenesis of retinal diseases, such as proliferative vitreoretinopathy (PVR), and may be associated with choroidal melanoma which lead to impairment or even loss of vision (Enzmann et al, 1998). Nothing is known about the signalling and the molecular mechanisms underlying these processes and we still know very little about the intracellular signalling that mediates RPE cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, despite the presence of FGF2 in the retinal interphotoreceptor matrix, retinal pigmented epithelial (RPE) cells have a limited proliferation capacity, corresponding to the normal increase in retinal space associated with growth and age. Increased levels of FGF2 with elevated levels of FGF2 excretion have been detected in cells derived from pigment cell tumors and RPE-associated choroidal melanomas in humans (Enzmann et al, 1998). Although RPE cells are unable to divide in vivo, they may still require survival factors to inhibit their apoptosis.…”
Section: Introductionmentioning
confidence: 99%